Electronic and structural characterization of barrier-type amorphous aluminium oxide. (10th January 2017) - Evangelisti, Fabio; Stiefel, Michael; Guseva, Olga; Partovi Nia, Raheleh; Hauert, Roland; Hack, Erwin; Jeurgens, Lars P.H.; Ambrosio, Francesco; Pasquarello, Alfredo; Schmutz, Patrik; Cancellieri, Claudia
Abstract: The structural, electronic, and dielectric properties of barrier-type anodic Al oxides prepared with various thicknesses have been investigated. The planar and cross morphologies as well as the surface charge distribution were investigated as a function of the voltage applied during growth, i.e. the thickness. Three distinct anodizing potential domains can be clearly identified. A transition in ionic mobilities induces, at anodizing voltage higher than 100 V, the built-up of space charge region in the anodic films. A correlated increased oxide density with growing anodization potential is consistently pointed out by Volta Potential Difference and XPS/Auger measurements. The full dielectric response of the oxides, including both the lattice and electronic components, has been accessed by electrochemical impedance spectroscopy and Auger analysis. The lattice contribution of the dielectric constant is found to be strongly affected by the growth voltage, as a clear increase in the lattice component of the dielectric constant is observed, reaching values close to those of bulk crystalline Al2 O3 structures. At variance, the electronic contribution is only slightly affected. The results have been compared to dielectric constants calculated for atomistic amorphous models within the framework of density functional theory. It is shown that amorphous Al2 O3 models of higher density lead to dielectric constants that could explain the trend observed in theseries of barrier-type anodic oxides prepared in this work.